2015
DOI: 10.1111/ijfs.12916
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different water types and brewing durations on the colloidal properties of green tea infusion

Abstract: Summary Green tea infusions were prepared with three different water types: distilled water, commercial mineral water and CaCl2 added distilled water (at 20 mg L−1). The impact of different water type on the colloidal particle parameters, namely size, polydispersity index (PDI) and zeta potential, was examined within 24 h. Our results indicate that distilled water green tea infusion (DWT) brewed at 80 °C for 5 min contained the smallest particles (242.17 ± 11.78 nm) as examined by dynamic light scattering (DLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Among all the samples, T-MIN showed the lowest a∗ values (−7.50), indicating that it had the darkest shade of green colour. This could be due to higher concentration of chlorophyll extracted in the sample [ 27 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among all the samples, T-MIN showed the lowest a∗ values (−7.50), indicating that it had the darkest shade of green colour. This could be due to higher concentration of chlorophyll extracted in the sample [ 27 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ktze.] infusion [103]. The average size of nanoparticles formed in a water extract of P. thomsonii Benth (Fenge) [104] or Rabdosia rubescens (Hemsl.)…”
Section: Factors Affecting Natural Nanoparticle Formationmentioning
confidence: 99%
“…34 On the other hand, Ca 2+ could compensate negative charges of tea nano-aggregates, resulting in the decrease of the electrostatic repulsion among colloidal particles and the flocculation of nano-aggregates. 35,36 Additionally, Ca 2+ would precipitate with oxalic acid, quinic acid, and tartaric acid in green tea infusions. 37 Thus, we proposed that the formation of tea cream particles involved the sedimentation of nano-aggregates resulting from the adsorption of methylxanthines from the supernatants onto the nano-aggregates via their associations with catechins as well as the flocculation among nano-aggregates due to the decrease of electrostatic repulsions induced by Ca 2+ .…”
Section: ■ Discussionmentioning
confidence: 99%
“…On the one hand, carbohydrates would increase the solubility of polyphenol–protein complexes, and pectin molecules would compete with proteins to bind with polyphenols, resulting in inhibition on the precipitation of polyphenol–protein complexes. , Hayashi et al confirmed that pectin would associate with various catechin monomers, whereas gallate-type was a preferable structure for pectin . On the other hand, Ca 2+ could compensate negative charges of tea nano-aggregates, resulting in the decrease of the electrostatic repulsion among colloidal particles and the flocculation of nano-aggregates. , Additionally, Ca 2+ would precipitate with oxalic acid, quinic acid, and tartaric acid in green tea infusions . Thus, we proposed that the formation of tea cream particles involved the sedimentation of nano-aggregates resulting from the adsorption of methylxanthines from the supernatants onto the nano-aggregates via their associations with catechins as well as the flocculation among nano-aggregates due to the decrease of electrostatic repulsions induced by Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%